PENGELOMPOKAN INDUSTRI MIKRO DI INDONESIA DENGAN METODE K-MEANS CLUSTERING - Aswan Sunge; Heri Hermawanto2 (Teknik Informatika, Universitas Pelita Bangsa, 2019)
Industry is part of the production sector that does not take these materials directly from nature for consumption but the materials are processed and finally become valuable and valuable to society. Micro industry is an industrial company whose workforce consists of 5-19 people. The purpose of this research is to classify the micro industry in Indonesia based on 3 clusters, namely the low cluster, medium cluster and high cluster using the K-Means Clustering method. The data used in this study is data on the number of micro industrial companies in Indonesia by province in 2013 - 2015. Based on this data, it was obtained that the regions with the number of micro industrial companies with low clusters (C0) were 31 provinces, medium cluster (C1) 2 provinces and clusters. height (C2) 1 province. Keywords : Industry, Clastering, Algoritma K-means